1985
DOI: 10.1111/j.1399-0039.1985.tb02225.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural HLA antibodies

Abstract: “Natural antibodies” directed against antigens of the Major Histocompatibility Complex have been observed in aged mice but very seldom in humans. It is likely that HLA natural antibodies are more common than previously supposed: our results suggest they may be found in 1% of normal blood donors. Most of these antibodies seem to be weak and can only be detected when B lymphocytes (BL) are used as target cells in the lymphocytotoxicity technique or when indirect immunofluorescence is used with peripheral blood l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…The prevalence of IgM that recognizes allo-HLA-Ia in the healthy sera without prior alloimmunization was documented previously (7). The present investigation further confirms the presence of IgM and IgG in healthy male sera reactive to HLA-Ia alleles coated onto different lots of SABs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of IgM that recognizes allo-HLA-Ia in the healthy sera without prior alloimmunization was documented previously (7). The present investigation further confirms the presence of IgM and IgG in healthy male sera reactive to HLA-Ia alleles coated onto different lots of SABs.…”
Section: Discussionsupporting
confidence: 89%
“…The progress made so far on the discovery of natural HLA Abs in humans projects that, in the future, a greater number and incidence of natural allo-HLA IgG Abs will be recorded in healthy nonalloimmunized males. A number of investigators provided different explanations for the presence of natural HLA Abs (7,11,12,43). Some contended that they are the result of a polyclonal, continuous immune response against exogenous Ags (5, 6, 8-12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it may contain HLA antibodies because several allo-HLA antibodies are known to occur naturally in the sera of both men (nonalloimmunized) and women. [9][10][11][12][13] MoralesBuenrostro et al 11 demonstrated the specificities and incidence of these allo-HLA-I Abs in nonalloimmunized males. Neither the origin nor cause of anti-HLA Abs occurring in healthy individuals has been established.…”
Section: Introductionmentioning
confidence: 99%